2019
DOI: 10.4103/jisp.jisp_383_18
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene status, oral hygiene practices and periodontal health of brick kiln workers of Odisha

Abstract: Aim and Objective:The aim of this study was to assess the oral hygiene status, oral hygiene practices, and periodontal health among brick kiln workers of Odisha.Materials and Methods:Four hundred and eight subjects (300 males and 108 females) between the ages of 22 and 65 years with mean age of 33.44 ± 2.34 years working in various brick kilns in the district of Khordha, Odisha, participated in the survey. Data were collected through personal interview and clinical examinations.Results:Overall prevalence of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“… 14 The frequency of brushing was reported “once daily” by most. This is similar to findings of Baishya et al 8 Asgari et al 16 El Bcheraoui et al 17 and Shah and ElHaddad. 18 Majority did not use dental floss or other interdental aids, similar to the same studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 14 The frequency of brushing was reported “once daily” by most. This is similar to findings of Baishya et al 8 Asgari et al 16 El Bcheraoui et al 17 and Shah and ElHaddad. 18 Majority did not use dental floss or other interdental aids, similar to the same studies.…”
Section: Discussionsupporting
confidence: 91%
“…The number of healthy sextants decreased with advancing age which is in accordance with available literature reporting increasing age with increasing severity of periodontitis. 2 , 3 , 7 , 8 , 21 , 22 , 24 About “Education”, majority of the sample were secondary and higher secondary above. One reason could be because of lack of oral health awareness in less educated individuals, they don't go to dental hospital unless they have to.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that the study population had the habit of using smokeless tobacco rather than smoking cigarettes and bidis. This-findings is similar to study done by Banashree Baishya et al (2013) [25] on study population of brick klin workers of odisha; most of the workers were found to be consuming paan or gutkha as compared to cigarette or beedis.…”
Section: Discussionsupporting
confidence: 91%
“…The number of males participated in our study was 68.7%. This can be correlated with a study conducted by Baishya B et al in 2019 [9] where 62.5% of participants were males. Dental caries is one of the most prevalent diseases across the world.…”
Section: Discussionsupporting
confidence: 89%